When is Mighty Gazprom Good for Russia? - Marina Tsygankova (Statistics Norway, Research Department, 2007)
In the late 1990s, several proposals for a structural reform that would bring competition and market prices to the Russian gas industry were intensely debated. Splitting up Russian gas monopolist Gazprom into several producing companies was a considered option. In this paper, I examine theoretically and numerically how a split-up of Gazprom would affect Russian national welfare. Results show that under the current gas market structures in Europe and Russia, the split-up of Gazprom's monopoly might not be beneficial for Russia. The market share of Russia in the European market is important in determining whether Gazprom's dominance is supported under the national welfare criteria.
Keywords: D43; L13; L11; L22; 330; Russia; Natural gas; restructuring reform; market share; national welfare